Postpartum behavioral profiles in Wistar rats following maternal separation - altered exploration and risk-assessment behavior in MS15 dams - Daoura, Loudin; Hjalmarsson, My; Oreland, Sadia; Nylander, Ingrid; Roman, Erika (Frontiers in Behavioral Neuroscience, 2010)
The rodent maternal separation (MS) model is frequently used to investigate the impact of early environmental factors on adult neurobiology and behavior. The majority of MS studies assess effects in the offspring and few address the consequences of repeated pup removal in the dam. Such studies are of interest since alterations detected in offspring subjected to MS may, at least in part, be mediated by variations in maternal behavior and the amount of maternal care provided by the dam. The aim of this study was to investigate how daily short (15 min; MS15) and prolonged (360 min; MS360) periods of MS affects the dam by examining postpartum behavioral profiles using the multivariate concentric square field™ (MCSF) test. The dams were tested on postpartum days 24-25, i.e. just after the end of the separation period and weaning. The results reveal a lower exploratory drive and lower risk-assessment behavior in MS15 dams relative to MS360 or animal facility reared dams. The present results contrast some of the previously reported findings and provide new information about early post-weaning behavioral characteristics in a multivariate setting. Plausible explanations for the results are provided including a discussion how the present results fit into the maternal mediation hypothesis.